(untitled) (Alternautas, 2022)
Hegemonic common sense suggests that a project as exotic as controlled economic degrowth is at its best applicable only in the geopolitical Global North while for the South, economic growth would be a requirement. Despite this, more and more voices are questioning the arguments that give economic growth a central place in political discussions, suggesting that this type of criticism could be liberating for many parts of the world (Max-Neef 1995; Latouche 2010; Altvater 2013; Muraca 2014; Gudynas y Acosta 2014; Lang 2016). The fifth international conference on degrowth that took place in Budapest, capital of Hungary, between the 30th of august and the 3rd of september 2016, revealed that reflections around degrowth are also a place of convergence for multiple transformatory narratives: from political ecology to ecological economics, considering also feminist perspectives that suggest the organization of society around a logic of care; from ideas of environmental and climate justice to policy ideas of universal and unconditional basic income. In this way, degrowth constitutes an additional contribution from a new internationalism, a contribution that seems necessary for interventions from the plural left over the globalized world. This internationalism is not limited to solidarity practices in struggles that take place in far away places, but instead, it looks for convergence, as well as complementarity and reciprocity between transformatory struggles that are contextualized and diverse.